PERUBAHAN GUNA LAHAN PORIS PLAWAD TANGERANG SEBAGAI KAWASAN TRANSIT-ORIENTED DEVELOPMENT (TOD) - Maulidya, Syifa; Permana, Chrisna Trie Hadi; Pujantiyo, Bambang S (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2024)
Urbanization in Jabodetabek is leading to an increase in the need for transportation. The 2018 Jabodetabek Transportation Master Plan (RITJ) aims to address this issue by planning transit-oriented development (TOD) areas throughout Jabodetabek, including the Poris Plawad transit-oriented development (TOD) area in Tangerang City. Once designated as a transit-oriented development (TOD) area, there should be changes in land use in Poris Plawad to suit the needs of the transit-oriented development (TOD) concept. Properly organizing land use around transportation nodes is essential for the success of transit-oriented development (TOD) projects. This study examines how land use has evolved over 11 years, before and after Poris Plawad was designated as a transit-oriented development (TOD) area. This research utilizes quantitative methods through descriptive analysis to compare Poris Plawad’s land use changes as a transit-oriented development (TOD) area. This research identifies the proportion of land use in the Poris Plawad transit-oriented development (TOD) area. The results indicate that the land use changes in Poris Plawad align with the transit-oriented development (TOD) concept. This indicates that before there was a policy regulating of Poris Plawad transit-oriented development (TOD) area, Poris Plawad's land use had the potential to become a transit-oriented development (TOD) area.